Mother's Perception of Implementing Cervical Cancer Prevention Behaviour Through HPV (Human Papilloma Virus) Vaccination - Agustini, Ni Komang Tri; Sagitarini, Putu Noviana; Dayu, Ida Ayu Ningrat Pangruating; Artsanthia, Jintana (Adi Husada Nursing Journal, 2024)
The high number of cervical cancer cases is still a big problem in Indonesia. Preventive measures that can be taken are early detection and vaccination against HPV (Human Papilloma Virus). However, the behavior of taking HPV vaccination is still low and is still influenced by several factors, according to the Health Belief Model theory, namely perception. This research is to identify and analyze perceptions using the Health Belief Model approach of HPV vaccination. The design used in this research is descriptive-analytical cross-sectional. The research was conducted in July-September 2023 at the Blahbatuh I Public Health Centre. The instrument used was a questionnaire about the mother's perception of the Health Belief Model with results reliability test 0.8614. Data were analyzed using SPSS with univariate and bivariate tests with Chi-Square. The components of the healing belief model that have a relationship with cervical cancer prevention behavior through HPV vaccination are perceived seriousness with p-value = 0.001 (p<0.05), perceived vulnerability with p-value = 0.001 (p<0.05), perceived benefits with p-value = 0.001 (p<0.05), perceived obstacles with p-value = 0.001 (p<0.05), and action to act with p-value = 0.001 (p<0.05). Maternal perceptions about the seriousness, susceptibility, benefits, barriers, and actions have a significant relationship with mother’s prevention behavior regarding HPV vaccination.